Analisis Daya Saing Komoditas Teh Hitam Curah Indonesia di Pasar Global (Studi Kasus di Negara Russia) - Galura Aqila Cakra; Jono M Munandar (Jurnal Manajemen dan Organisasi, 2020)
Brewed tea is the most consumed beverage after water. The tea commodity is divided into four: bulk green tea, retailed green tea, bulk black tea, and retailed black tea. Eventhough bulk black tea has the lowest price average, it has the highest demand and import value growth each year. Rusia is not only the main export destination country for Indonesian bulk black tea, but also the largest bulk black tea importer in the world. The purpose of this research are to analyze the position of Indonesian bulk black tea export competitiveness in the global market and to find the factors that significantly affect Indonesian bulk black tea export in Russian market. The result of CMSA shows that Indonesia's competitiveness ranks low among other exporter countries and has a negative growth trend. According to multiple linear regression analysis, the most significantly affecting factor is price with a negative relation. Which means when price grows, Indonesia's competitiveness decline.